Response of Soil Fungal Community Structure to Long-Term Continuous Soybean Cropping - Liu, Hang; Pan, Fengjuan; Han, Xiaozeng; Song, Fengbin; Zhang, Zhiming; Yan, Jun; Xu, Yanli (Frontiers in Microbiology, 2019)
Long-term continuous soybean cropping can lead to the aggravation of soil fungal disease. However, the manner in which the fungal community and functional groups of fungi are affected by continuous soybean cropping remains unclear. We investigated the fungal abundance, composition and diversity during soybean rotation (RS), 2-year (SS) and long-term (CS) continuous soybean cropping systems using quantitative real-time PCR and high-throughput sequencing. The results showed that the fungal abundance was significantly higher in CS than in SS and RS. Long-term continuous soybean cropping altered the fungal composition. Compared with RS, SS had an increase of 29 and a decrease of 12 genera in fungal relative abundance, and CS increased 38 and decreased 17 genera. The Shannon index was significantly higher in CS and SS than in RS. The result of principal coordinate analysis (PCoA) showed that CS and SS grouped together and were clearly separated from RS on the PCoA1. A total of 32 features accounted for the differences in fungal composition across RS, SS and CS. The relative abundance of 10 potentially unfavorable and 10 potentially favorable fungi changed, and most of their relative abundances dramatically increased in SS and CS compared with RS. Our study indicated that long-term continuous soybean cropping results in selective stress on unfavorable and favorable fungi and causes the development of the fungal community structure that is antagonistic to plant health.